how do I do this (1 Viewer)

Sylfiphy

New Member
Joined
Feb 5, 2024
Messages
14
Gender
Undisclosed
HSC
2025
not to be dumb or anything but can someone explain how to work this out

If, f(x)= f(x+1) + x^2 , and f(3)=7, evaluate f(1)
 

scaryshark09

Well-Known Member
Joined
Oct 20, 2022
Messages
1,831
Gender
Undisclosed
HSC
1999
first let x = 2

f(2) = f(2+1) + 2^2
f(2) = f(3) + 4
f(2) = 7 + 4 [ since f(3)=7 ]
f(2) = 11

now let x = 1

f(1) = f(1+1) +1^2
f(1) = f(2) + 1
f(1) = 11 + 1 [ since f(2)=11 ]
f(1) = 12
 

Sylfiphy

New Member
Joined
Feb 5, 2024
Messages
14
Gender
Undisclosed
HSC
2025
first let x = 2

f(2) = f(2+1) + 2^2
f(2) = f(3) + 4
f(2) = 7 + 4 [ since f(3)=7 ]
f(2) = 11

now let x = 1

f(1) = f(1+1) +1^2
f(1) = f(2) + 1
f(1) = 11 + 1 [ since f(2)=11 ]
f(1) = 12
yeah but maybe I’m js tweakin here but the answer sheet says the answer is -6 ??? how did they get that cuz I did the same working as u
 
Joined
Jul 14, 2023
Messages
20
Location
Bundaville 😋😋😋
Gender
Male
HSC
2023
not to be dumb or anything but can someone explain how to work this out

If, f(x)= f(x+1) + x^2 , and f(3)=7, evaluate f(1)
Alright
First, you rearrange it into f(x + 1) = f(x) - x^2, I swapped the order cause it is easier to work with

f(3) = f(2 + 1) = 7
Now from the f(x+1) equation you can say f(2 + 1) = f(2) - 2^2 = 7
f(2) - 4 = 7

so f(2) = 11
f(2) = f(1 + 1) = 11

From the f(x + 1) function again, f(1 + 1) = f(1) -1^2 = 11
f(1) - 1 = 11

So f(1) = 12

If there are any errors here I am sorry, I am kinda sleepy, but the logic should lead to the right answer.
I haven't seen a question like this in ages.
 

rev668

New Member
Joined
Jul 18, 2023
Messages
29
Gender
Male
HSC
2024
not to be dumb or anything but can someone explain how to work this out

If, f(x)= f(x+1) + x^2 , and f(3)=7, evaluate f(1)
To evaluate \( f(1) \) using the given functional equation \( f(x) = f(x+1) + x^2 \) and the initial condition \( f(3) = 7 \), we can employ a method that involves iteratively substituting values and recursively solving the equation.

Let's start by utilizing the initial condition to find \( f(2) \):
\[ f(2) = f(3) + 2^2 = 7 + 4 = 11 \]

Now, having found \( f(2) \), we can proceed to find \( f(1) \):
\[ f(1) = f(2) + 1^2 = 11 + 1 = 12 \]

This approach leverages the recursive nature of the given functional equation, where each \( f(x) \) is dependent on \( f(x+1) \) and the value of \( x^2 \). By successively substituting values, we can trace back to find \( f(1) \) from the initial condition.

It's worth noting that this process can be extended further to evaluate \( f(0) \), \( f(-1) \), and so forth, depending on the domain of the function and the range of values of interest.

Therefore, the value of \( f(1) \) is \( 12 \). This solution method provides a systematic approach to solving for \( f(1) \) and showcases the step-by-step process involved in leveraging the given functional equation and initial condition to find the desired value.
 

ExtremelyBoredUser

Bored Uni Student
Joined
Jan 11, 2021
Messages
2,525
Location
m
Gender
Male
HSC
2022
yeah but maybe I’m js tweakin here but the answer sheet says the answer is -6 ??? how did they get that cuz I did the same working as u
dw bro some answer sheets esp random ones off online be dodgy as hell, my stupid ass spent an hour on a question rigorously proving i was right and assumed i was wrong, then just realised the answers were wrong. Best thing u can do is just to ask other ppl and if ur acc wrong, theyll most likely point it out.
 

Users Who Are Viewing This Thread (Users: 0, Guests: 1)

Top